The First Infant Bloodstream Infection Caused by Pantoea dispersa in China: A Case Report and Literature Review - Yu W; Sun Z; Wang M; Li Z; Zhang C; Sun Y; Wang S (Infection and Drug Resistance)
Wenwen Yu,1,2 Zhaohui Sun,3 Mengyuan Wang,1,2 Zheng Li,1,2 Chunyan Zhang,1,2 Yanmeng Sun,1,2 Shifu Wang1,2 1Department of Clinical Microbiology, Children’s Hospital Affiliated to Shandong University, Jinan Children’s Hospital, Jinan, 250022, People’s Republic of China; 2Shandong Provincial Clinical Research Center for Children’s Health and Disease, Jinan, 250022, People’s Republic of China; 3Department of Ultrasound, Zhaoyuan People’s Hospital, Yantai, People’s Republic of ChinaCorrespondence: Shifu Wang, Email wshfu709@163.comAbstract: Pantoea is a prevalent environmental Gram-negative bacterium comprising over 20 distinct species. It is a facultative anaerobe capable of forming smooth, translucent colonies on culture plates. Pantoea is typically considered a potential pathogen that may cause infections in plants and animals. With the advancement in mass spectrometry and gene sequencing technologies, human infections caused by Pantoea have increasingly been recognized, raising concerns regarding its pathogenicity and nosocomial transmission that clinicians must address. While there are numerous reports documenting P. agglomerans as a cause of human infections in clinical settings, instances of P. dispersa leading to human pathogenesis are comparatively rare, and the clinical manifestations associated with P. dispersa infections remain largely underexplored. We report a case of a 9-month-old female patient from China whose blood cultures indicated positive Gram-negative bacilli. Through MALDI Biotyper and next-generation sequencing techniques, the pathogen was identified as P. dispersa. Clinically, meropenem was administered for treatment, and the patient’s condition improved. We hope this article will help clinicians pay more attention to and better understand infant-related bloodstream infections caused by P. dispersa.Keywords: Pantoea dispersa, bloodstream infection, case report, infant, China